Preparation of phosphorus-containing cyanate resin with low curing temperature while excellent flame resistance and dielectric properties. Issue 7 (3rd July 2019) - He, Jie; Hou, Defa; Ma, Hanbing; Li, Xiuyun; Li, Dan
Abstract: A novel cyanate resin was prepared by the reaction of 10-(2, 5-Dihydroxyphenyl)-10-H-9-oxa-10-phospha-phenantbrene-10-oxide (DOPO-HQ) and 2, 2-Bis (4-cyanatophenyl) propane (BACY) when trace of cobalt(III) acetylacetonate(CoAt(III)) was added, The curing behavior during the reaction of DOPO-HQ/BACY/CoAt(III) system was analyzed by gelation time (GT), differential scanning calorimetry (DSC) and Fourier transformation infrared spectrometry (FTIR), respectively. Compared with the BACY/CoAt(III) system (GT = 1239 s, T p (exothermic peak temperature) = 215 °C), the GT of DOPO-HQ/BACY/CoAt(III) system is 110 s at 180 °C, and the T p is 154 °C when containing 10 wt % DOPO-HQ. The limit oxygen index (LOI) and vertical burning test (UL-94) demonstrate that the flame retardancy of BACY resin is improved by DOPO-HQ. Specifically, the DOPO-HQ/BACY resin prepared by a mass ratio of DOPO-HQ: BACY = 10:90 has a LOI value of 33.1% and a UL-94 of V-0 rating, while the LOI value of BACY resin is 28.5% and UL-94 is no rating. In addition, the DOPO-HQ/BACY resin containing 10 wt % DOPO-HQ has excellent dielectric properties, the dielectric constant (D k ) is 2.69 and dielectric loss (D f ) is 0.007. The as-synthesized DOPO-HQ/BACY resin shows promising application prospect as electronic packaging materials.